Innovation Capability: The Role of Positional Advantage, Visual Aesthetics, and Generational Cohort in SMEs’ Competitiveness - Pancanugraha, Indra; Bachri, Syamsul; Wahyuningsih; Syamsuddin; Sutomo, Maskuri (Jurnal Aplikasi Manajemen, 2025)
In competitive markets, innovation capability is critical in enhancing marketing strategies. The present study analyzes the effect of innovation capability on marketing performance outcome with visual aesthetics and positional advantage as mediating variables, and generational cohort as a moderating variable. The population of this study comprised 113 respondents from weaving and batik small-to-medium enterprises (SMEs) in Central Sulawesi, who were selected through a census sampling method. The data were collected through the administration of questionnaires and subsequently analyzed using the Smart PLS 4 application to evaluate the relationships in the conceptual model. The findings suggest that innovation capability exerts a negative and non-significant influence on marketing performance. However, visual aesthetics and positional advantage have been shown to significantly enhance the impact of innovation capability on marketing performance. Subsequent findings demonstrate that visual aesthetics significantly enhances positional advantage. The generational cohort substantially moderates the relationship between innovation capability and marketing performance. This study posits that when employed as a marketing strategy, local wisdom can be a source of competitive advantage by leveraging visual elements derived from unique cultural symbols. As evidenced by the study's findings, this approach can be convenient in dynamic marketplaces where imitation is challenging. Generational groups exhibit divergent capacities for innovation within small- and medium-sized enterprises (SMEs), which can result in disparities in their ability to attain competitive advantage.